2022
DOI: 10.3390/foods11182818
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Cold Plasma Technology on Sensory, Nutritional and Safety Quality of Food: A Review

Abstract: As an emerging non-thermal food processing technology, cold plasma (CP) technology has been widely applied in food preservation due to its high efficiency, greenness and lack of chemical residues. Recent studies have indicated that CP technology also has an impressing effect on improving food quality. This review summarized the impact of CP on the functional composition and quality characteristics of various food products. CP technology can prevent the growth of spoilage microorganisms while maintaining the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 117 publications
0
14
0
Order By: Relevance
“…The reason for the higher respiratory intensity in the 80 kV treatment group may be the fact that the 80 kV treatment produced more active substances and created an environment higher in reactive oxygen species compared with the 40 kV and 60 kV treatments. Zhang et al found that high-intensity ACP treatment produced more active substances [ 25 ]. As shown in Figure 1 B, the firmness of the tomatoes decreased with the prolongation of the storage time, and the firmness of the control group was significantly lower than that of the treatment group ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The reason for the higher respiratory intensity in the 80 kV treatment group may be the fact that the 80 kV treatment produced more active substances and created an environment higher in reactive oxygen species compared with the 40 kV and 60 kV treatments. Zhang et al found that high-intensity ACP treatment produced more active substances [ 25 ]. As shown in Figure 1 B, the firmness of the tomatoes decreased with the prolongation of the storage time, and the firmness of the control group was significantly lower than that of the treatment group ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…According to Zhang et al (2022) findings, as the traditional chemical agent in meat (nitrite) is replaced by CP-generated species, CPtreated meat products are more vibrant red than untreated samples (Zhang et al, 2022). In addition, Koddy et al (2021) reported that CP treatment increases the brightness value of hairtail samples due to the increase in hairtail muscle proteins' water-holding capacity in treated samples (Figure 6) (Koddy et al, 2021).…”
Section: How Cold Plasma Affects Myoglobinmentioning
confidence: 99%
“…Moreover, the carrier gases employed in CP technology typically consist of oxygen, nitrogen, air, inert gases, or gas mixtures. Among these, air stands out as an economical working gas that finds extensive application in the food industry (Zhang, Tan, et al., 2022).…”
Section: Nonthermal Physical Field Technologiesmentioning
confidence: 99%